Towards environmental performance through responsible environmental intentions and behavior: Does environmental law cognition really matter among Chinese farmers - Wang, Ying (PloS one, 2024)
Rapid agricultural expansion, marked by unsustainable practices, has contributed significantly to environmental degradation globally. In response to China’s escalating environmental concerns, recent environmental legislation has sought to disseminate information and promote awareness of environmental preservation among residents. This study aims to investigate the influential role of citizen environmental intentions and activist environmental intentions on responsible behavior for achieving environmental performance (EP). Moreover, the moderating influence of these environmental laws on the relationship between environment-protecting intentions and behavior, with a focus on legal cognition. Utilizing a population of 3150 farmers we select 603 farmers using simple random sampling and, this study applies the theory of planned behavior within a structural equation model framework. The findings affirm that farmers’ perceived behavior control, personal factors, and attitudes directly impact both citizen and activist intentions, subsequently influencing both types of environmental-oriented behavior. Notably, the study identifies a stronger inward attitude effect compared to the outward attitude in both types of farmers’ intentions. Additionally, legal cognition among farmers emerges as a crucial moderator, influencing the link between environmental intentions and behavior. The results suggest that as farmers become more familiar with environmental laws, the direct effect of their intentions on environmentally oriented behavior intensifies. Hence, the legal obligations play an essential role in shaping the farmers’ pro-environmental behavior. This study aligns the individual level environmental intentions with farmer’s law cognition for offering interesting insights to develop and implement imminent environmental policies. Hence, this study benefits to both practitioners and policy makers’ contextualizing Chinese agricultural sector.